An Electrically Tunable Dual-Wavelength Refractive Index Sensor Based on a Metagrating Structure Integrating Epsilon-Near-Zero Materials - Zhenya Meng; Hailin Cao; Run Liu; Xiaodong Wu (Sensors, 2020)
In this paper, a reconfigurable sensing platform based on an asymmetrical metal-insulator-metal stacked structure integrating an indium tin oxide (ITO) ultrathin film is proposed and investigated numerically. The epsilon-near-zero (ENZ) mode and antisymmetric mode can be resonantly excited, generating near-perfect absorption of over 99.7% at 1144 and 1404 nm, respectively. The absorptivity for the ENZ mode can be modulated from 90.2% to 98.0% by varying the ENZ wavelength of ITO by applying different voltages. To obtain a highly sensitive biosensor, we show that the proposed structure has a full-width at half-maximum (FWHM) of 8.65 nm and a figure-of-merit (FOM) of 24.7 with a sensitivity of 213.3 nm/RI (refractive index) for the glucose solution. Our proposed device has potential for developing tunable biosensors for real-time health monitoring.